ANALISIS KOSAKATA DONGENG “SI KABAYAN JADI DUKUN” DALAM KEMAMPUAN BERBAHASA SUNDA SISWA SEKOLAH DASAR: STUDI LITERATUR - Aldavia Thursina; Febby Deca Lestari; Meyra An Najmi; Nabila Wanda Yusela; Indah Nurmahanani (STKIP Subang, 2026)
This study aims to analyze the vocabulary found in the folktale Si Kabayan Jadi Dukun and its relation to the Sundanese language skills of elementary school students. Sundanese folktales are one form of regional literature that can be utilized as a medium for language learning because they contain vocabulary, expressions, and cultural values closely related to the daily lives of the Sundanese community. This study employed a descriptive-analytical method with a literature study approach. Data were obtained through the examination of various sources, such as books, scientific journals, articles, and documents related to Sundanese folktales, vocabulary, and Sundanese language learning in elementary schools. The results show that the folktale Si Kabayan Jadi Dukun contains a variety of Sundanese vocabulary that is communicative, contextual, and reflective of Sundanese cultural values. The vocabulary found in the folktale can be used to improve students’ listening, speaking, reading, and writing skills. In addition, the use of regional folktales in learning activities can help increase students’ interest in the Sundanese language and support the preservation of regional culture. Therefore, Si Kabayan Jadi Dukun has strong potential as a relevant and educational source for Sundanese language learning for elementary school students.